Binderless low silica X zeolite for methane separation from binary CO2/CH4 biogas stream: A comprehensive experimental and computational study - Yadav, Tushar R.; Shrotri, Aadesh R.; Kate, Pranjali N.; Devasia, George; Niphadkar, Prashant S.; Mali, Nilesh A.; Krishnamurty, Sailaja; Bokade, Vijay V.; Nandanwar, Sachin U. (Journal of Industrial and Engineering Chemistry, 2025)
This study presents the synthesis of binderless Na-LSX (B-Na-LSX) and binderless NaK-LSX (B-NaK-LSX). XRD, SEM, EDS, and N-2 physisorption were used for characterization of samples. Computational modelling of prepared sorbent was performed for the fundamental understanding of zeolite topology and adsorption behaviour. The breakthrough experiments are used to evaluate the adsorption capacities on CO2/CH4 (40/60 vol%) binary biogas stream. The results were compared with commercial Na-LSX (C-Na-LSX). The breakthrough adsorption capacity of B-Na-LSX was 3.08 mmol g(-1) and 0.29 mmol g(-1) of CO2 and CH4, respectively, at 300 K and 1 bar. CO2 sorption capacity of B-Na-LSX was similar to 11 % and similar to 17 % higher than B-NaK-LSX (2.77 mmol g(-1)) and C-Na-LSX (2.56 mmol g(-1)), respectively. DFT study reveals that the higher adsorption of CO2 over CH4 was attributed to higher charge transfer from CO2 to zeolite framework. Dual-bed six-step Pressure Swing Adsorption (PSA) was performed on B-Na-LSX at 6 bar. similar to 232 cycles were run with above 98 % of CH4 purity and similar to 74 % of recovery. The life-cycle test of sorbent was studied. It was implied that the designed sorbent is effective to produce the high purity of CH4 and can be utilized for a longer period for CH4 production.
Keywords: Binderless; Biogas; LSX zeolite; methane; PSA; Separation